Cervical arthritis, C3-C7, from an identified osteological collection - Quispe, Breidy I. (2019)
Osteoarthritis on the cervical vertebrae, C3-C7, accumulates as a function of age, life style, diet and severity of long-term skeletomuscular stress. However, the degree to which age (older adult and elderly) and sex differences impact on the manifestation of osteoarthritis remains difficult to assess because of the variability of biological aging and the lack of discrete post-reproductive age categories. The aim of this investigation was to score the degree of osteophytic marginal lipping, porosity and eburnation on the cervical vertebrae of identified individuals from the William M. Bass Donated Skeletal Collection of the Forensic Anthropology Center of the University of Tennessee, Knoxville, USA, to address whether the expression of osteoarthritic features differs (1) between older adults, 50-55 years, and elderly adults, 70-76 years, within each sex; (2) between both sexes of the same William M. Bass Donated Skeletal Collection age category; and (3) between the sexes regardless of age. Osteological remains included were accessioned between 2000 and 2010 to reflect contemporary variation, and only C3 to C7 were scored given the distinctions in morphology and function of the atlas and axis. The vertebrae were separated by number and analyzed using Mann-Whitney U tests. Osteoarthritic features are generally more severe in males compared to females although eburnation is elevated in older females (50-55 years) compared to their elderly counterparts (70-76 years). Both sexes show an accumulation of osteoarthritic features as a consequence of advancing age. However, sex differences between elderly adults (70-76 years) are less extreme compared to when all females and males are considered regardless of age.